Transport of laser accelerated proton beams and isochoric heating of matter - Roth, M; Alber, I; Bagnoud, V; Brown, C; Clarke, R; Daido, H; Fernandez, J; Flippo, K; Gaillard, S; Gauthier, C; Glenzer, S; Gregori, G; et al. (2010)
The acceleration of intense proton and ion beams by ultra-intense lasers has matured to a point where applications in basic research and technology are being developed. Crucial for harvesting the unmatched beam parameters driven by the relativistic electron sheath is the precise control of the beam. We report on recent experiments using the PHELIX laser at GSI, the VULCAN laser at RAL and the TRIDENT laser at LANL to control and use laser accelerated proton beams for applications in high energy density research. We demonstrate efficient collimation of the proton beam using high field pulsed solenoid magnets, a prerequisite to capture and transport the beam for applications. Furthermore we report on two campaigns to use intense, short proton bunches to isochorically heat solid targets up to the warm dense matter state. The temporal profile of the proton beam allows for rapid heating of the target, much faster than the hydrodynamic response time thereby creating a strongly coupled plasma at solid density. The target parameters are then probed by X-ray Thomson scattering (XRTS) to reveal the density and temperature of the heated volume. This combination of two powerful techniques developed during the past few years allows for the generation and investigation of macroscopic samples of matter in states present in giant planets or the interior of the earth. © 2010 IOP Publishing Ltd.